Influencia de los gansos en el combate de malezas y en la fertilizacion organica de estanques piscicolas - Arroyo, C.L.=700 1 Ruiz, R.
(Es, En)
Ilus., 4 ref.
Keywords: ABONOS ORGANICOS; ESTIERCOL; GANSO; PRODUCTIVIDAD; FITOPLANCTON; ZOOPLANCTON; CRECIMIENTO; MALEZAS; COSTA RICA; AGRONOMIA COSTARRICENSE